2018
DOI: 10.1001/jamapsychiatry.2018.0385
|View full text |Cite
|
Sign up to set email alerts
|

Physical Inactivity and Mental Health in Late Adolescence

Abstract: Late adolescence, between the ages of 15 and 19 years, represents a critical stage in life in which young people develop a sense of identity and independence as they transition to adulthood. This stage in life also involves pressures of maturation, academic performance expectations, and changing social roles. Compound these pressures with economic and psychosocial adversity in childhood and early adolescence, including abuse and neglect at home or racial/ethnic, gender, and sexual discrimination, and there eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 7 publications
2
24
1
2
Order By: Relevance
“…The field of anxiety research in physical activity is in need of further development. Overall, we concur with a recent call for greater policy emphasis on physical activity for young people, based on the assertion that "the scientific evidence suggests that regular physical activity protects against deficits in mental health and supports cognitive function" (Beauchamp, Puterman, & Lubans, 2018 Comments: Part of a wideranging review of health outcomes of PA. Conclusions (below) seem optimistic given evidence summarised.…”
Section: Resultssupporting
confidence: 75%
“…The field of anxiety research in physical activity is in need of further development. Overall, we concur with a recent call for greater policy emphasis on physical activity for young people, based on the assertion that "the scientific evidence suggests that regular physical activity protects against deficits in mental health and supports cognitive function" (Beauchamp, Puterman, & Lubans, 2018 Comments: Part of a wideranging review of health outcomes of PA. Conclusions (below) seem optimistic given evidence summarised.…”
Section: Resultssupporting
confidence: 75%
“…higher self-rated mental health, and [35], who reached similar conclusions as us in a concurrent but methodologically distinct analysis of the same Add Health cohort. Our findings also accord with the broader literature on the benefits of adolescent physical activity [60]: regular physical activity during adolescence may decrease the risk of diabetes [61] and obesity [62], improve psychological and social health [26], and may even protect against later-life neurodegeneration [63]. Additionally, our finding that any adverse adolescent football participation might not manifest in early adulthood is similar to [64] finding that participating in tackle football before age 12 may not result in short-term neurocognitive deficits in college.…”
Section: Plos Onesupporting
confidence: 90%
“…Worldwide the prevalence of mental disorders like depression increases markedly during late adolescence reaching peak during early adulthood which is age 20-24 years. 14 In Caribbean population, female adolescence was significantly associated with the reporting of depression, 13 but there was no association between gender and depression in this study. Studies done on American adolescents has shown that suicide related behavior increases with age, 15 which is similar to the findings of our study where the number of subjects in late adolescence having thoughts of self harm and suicide was six times more than that of early adolescent age group.…”
Section: Discussioncontrasting
confidence: 53%